An Overview of Genetic Disorder in Current Scenario w.s.r Beeja Dosha Theory - Ankita Tiwari; Nitish Sharma (AYUSHDHARA, 2024)
Ayurveda is an old wisdom of life and health, the different branches of Ayurveda have evolved over the period of time as health being substantially concerned with precluding as well as curing the conditions. With adding capability to control contagious complaint and nutritive complaint there has come one realisation that the inheritable diseases are the major cause of disability, death and mortal tragedy. The inheritable diseases are the high obstacles in the development of mortal being. The causative factors for these diseases as are the indecorous conformation of genotype. Ayurvedic Samhitas also stated about the inheritable complaint as Beejdosha Vikara and also there's elaboration about concurrence of Beeja Dosha. In Ayurveda there's explanation of Ritu, Kshetra, Ambu, Beej as four effects essential for confirmation of embryo and its development. The pathological change in any one of stage leads to indecorous conformation of embryo and its development. To avoid this script the Ayurveda explained the preventative measures as sanctification remedy and drug.